The Revised Identity Style Inventory: Factor Structure and Validity in Italian Speaking Students - Monacis, Lucia; de Palo, Valeria; Sinatra, Maria; Berzonsky, Michael D. (Frontiers in Psychology, 2016)
The purpose of this study was to evaluate the factor structure and convergent and discriminant validity of scores on an Italian translation of the Revised Identity Style Inventory (ISI-5) with samples of 237 adolescents (50 males, Mage = 18.04, SD = .86) and 268 university students (42 males, Mage = 22.71, SD = 3.70). Confirmatory Factor Analysis (CFA) indicated that a three-factor solution provided a good fit, which was invariant across age and sex groups. The theoretically relationships between scores on the Identity Style Inventory and scores on measures of reasoning and identity processes, identity commitment, and social desirability were partially consistent, thus further studies are needed to give more evidence to the convergent and discriminant validity.